MEDIA PEMBELAJARAN DALAM LANTUNAN AYAT SUCI AL-QURâ€™AN DENGAN PEMBAHASAN SURAH MAKKIYAH (SURAT PENDEK) PADA SD IT AL-MUTHMAINNAH : Learning Media;Tahfidz Qur'an;SD IT;Adobe Flash CS 5.Â - Surya, Junaidi; Adriana, Windy; Riana, Ulfa (LP2M Universitas Nurdin Hamzah, 2022)
Learning Tahfidz Qur'an in SD IT Al-Muthmainnah Jambi City has not been able to hold learning tahfidz / memorize Al-Qur'an effectively because the system used is not optimal. besides students get the material tahfidz, students are also given tajwid material. The material given is Al-Qur'an juz 30. Tahfidz Qur'an method of learning in SD IT Al-Muthmainnah Jambi City using a manual method. The given material is an optional rote and memorization. Memorization must be determined by the teacher Tahfidz Qur'an of each class. And the rote choice is memorization that has been achieved by each student. For that the authors make a computerized system design Learning Media using the application adobe flash cs 5 on SD IT Al-Muthmainnah Jambi City which aims to assist the school in providing materials in a more interesting way and make it easier for students to understand the lesson.